Comparison of static and mobile antibiotic-impregnated cement spacers for the treatment of infected total knee arthroplasty - Park, Sang-Jin (Springer-Verlag, 2009)
Infection after total knee arthroplasty (TKA) is a devastating complication, and two-stage reimplantation has evolved as an effective treatment option. This study was undertaken to compare the clinical results and radiological changes associated with static or mobile cement spacer placement for the treatment of infected TKA. Between July 2000 and February 2007, 36 consecutive patients were treated by two-stage reimplantation using antibiotic-impregnated cement spacers (AICS) for infected TKAs. Static spacers were used in 20 knees and mobile spacers in 16 knees. Clinical outcomes included success rates of TKR revisions, ranges of motion (ROM), and Hospital for Special Surgery knee scores (HSS), pain and function scores of the Knee Society (KS), joint exposure methods, and bone loss. In this study, mobile spacers provided better ranges of motion and functional knee scores without concomitant increases in infection rate and bone loss in the initial and mid-term periods.